A radiocalibration method with pseudo internal standard to estimate circulating metabolite concentrations. (July 2010) - Yi, Ping; Luffer-Atlas, Debra
Background: It has become important for metabolism scientists to identify and quantify prominent circulating human metabolites in order to develop a metabolite safety-qualification package that meets regulatory standards. Often these metabolites cannot be analyzed using traditional bioanalytical methods because a standard is not available.Results: A radiocalibration method is described that can estimate circulating metabolite concentrations in nonradioactive human and animal plasma. The key to this method is application of a pseudo internal standard (PIS) that is present in both radioactive reference and nonradioactive (i.e., unknown) samples. Metabolite exposure in the unknown samples is estimated from measured PIS exposure using a relative molar ratio established between the metabolite and PIS (usually parent drug).Conclusion: Two case studies demonstrate that the method can be used to establish human metabolite safety coverage in animal plasma and method validation is demonstrated by comparing estimated metabolite concentrations in human plasma with concentrations obtained directly using a metabolite calibration curve.